Effectiveness of CoronaVac in a pioneer risk-based allocation clinical trial during the COVID-19 pandemic - Alex Martins; Mario Felipe Bosco Santos; Joabi Nascimento; Fabíola Mendonça da Silva Chui; Maria Gabriela Almeida Rodrigues; Talita Bastos; Sonia Lemos; Eduardo Honorato; Márcio Cortez; Mariana Simão Xavier; Erika Oliveira Gomes; Rebeca Linhares Abreu-Netto; et al. (PLoS ONE, 2026)
CoronaVac, an inactivated SARS-CoV-2 vaccine, was one of the first deployed during the COVID-19 pandemic. Given the limited vaccine availability and the urgent need to assess effectiveness in target populations, a risk-based allocation clinical trial was designed to generate evidence under the ethical and logistical constraints at the beginning of the COVID-19 vaccination. In Manaus, Brazil, participants working in public service (education and public safety) aged 18–49 years were assessed regarding the risk of severe COVID-19 disease. Participants with one or more comorbidities, who were considered at higher risk of severe COVID-19 outcomes if infected, were allocated to early vaccination, while participants without comorbidities were enrolled as an unvaccinated comparison group. Blood samples were collected before each vaccine dose (D0 and D28) and during in-person follow-up visits (D90 and D180). Additional information was obtained through phone calls. Clinical cases of COVID-19, hospitalizations, deaths, and antibody titrations were the evaluated endpoints, considered after the second week following the second dose of the vaccine. A total of 6,226 participants were included: 1,139 in the low-risk group, and 5,087 in the high-risk vaccinated group. COVID-19 incidence was statistically significantly lower ( p < 0.001) in the vaccinated group at D28 (5.2% vs. 40.9%) and D90 (10.3% vs 31.6%). Hospitalization and death rates were low, with no difference observed between the groups. There was a decline in highly reactive titers at D180 in the vaccinated group. This pioneer risk-based allocation clinical trial provided evidence that CoronaVac reduced the risk of severe COVID-19 outcomes among individuals with comorbidities, effectively aligning their risk with that of lower-risk, unvaccinated individuals. Beyond its clinical implications, the study underscores the importance of adaptive, real-world research designs in rapidly generating actionable evidence in response to emerging public health threats. ClinicalTrials.gov Registration: NCT04789356